APLIKASI MODEL PEMBELAJARAN UNTUK MENDUKUNG KEGIATAN BELAJAR MENGAJAR - Hasbullahair Ashar (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2011)
This paper is a fieldwork study developed by a critical analysis of library research. The purpose of the writing is, firstly, to develop teachers’ understanding on learning models in the teaching process. Secondly, this study encourages teachers to develop teaching instrument to achieve the national education goal. The main issue of this study is, firstly, an understanding of important elements of the terms model, strategy, approach, method and technique. The second is a description of some learning models and the implementation pro-cedures in teaching process. This study applies library approach based on the field phenomenon. The expected implication is to enrich rea-ders’ perception in order that they become professional teachers.